Skeletal muscle repair in a mouse model of nemaline myopathy - Sanoudou, Despina (2006)
Nemaline myopathy (NM), the most common non-dystrophic congenital myopathy, is a variably severe neuromuscular disorder for which no effective treatment is available. Although a number of genes have been identified in which mutations can cause NM, the pathogenetic mechanisms leading to the phenotypes are poorly understood. To address this question, we examined gene expression patterns in an NM mouse model carrying the human Met9Arg mutation of alpha-tropomyosin slow (Tpm3). We assessed five different skeletal muscles from affected mice, which are representative of muscles with differing fiber-type compositions, different physiological specializations and variable degrees of pathology. Although these same muscles in non-affected mice showed marked variation in patterns of gene expression, with diaphragm being the most dissimilar, the presence of the mutant protein in nemaline muscles resulted in a more similar pattern of gene expression among the muscles. This result suggests a common process or mechanism operating in nemaline muscles independent of the variable degrees of pathology. Transcriptional and protein expression data indicate the presence of a repair process and possibly delayed maturation in nemaline muscles. Markers indicative of satellite cell number, activated satellite cells and immature fibers including M-Cadherin, MyoD, desmin, Pax7 and Myf6 were elevated by western-blot analysis or immunohistochemistry. Evidence suggesting elevated focal repair was observed in nemaline muscle in electron micrographs. This analysis reveals that NM is characterized by a novel repair feature operating in multiple different muscles.